2013
DOI: 10.1115/1.4024982
|View full text |Cite
|
Sign up to set email alerts
|

Drag Reduction Using Riblet Film Applied to Airfoils for Wind Turbines

Abstract: This paper presents results of a study that was commissioned by the 3M Renewable Energy Division to measure the drag reduction by using riblet film on airfoils specifically designed for wind turbine applications. The DU 96-W-180 airfoil was tested with four different symmetrical V-shaped riblet sizes (44, 62, 100, and 150-μm) at three Reynolds numbers (1 × 106, 1.5 × 106, and 1.85 × 106) and at angles of attack spanning the low drag range of the airfoil. Tests were run with riblet film covering different secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 10 publications
4
36
1
Order By: Relevance
“…On the upper wing the lower side is split in two pressure levels and the lowest differential pressure is approximately at the maximum chord thickness. figure 4, below, the leading edge disturbance, on the right, and how far behind the trailing edge where laminar flow returns [11]. These match and support the results of pressure distribution in figure 3.…”
Section: Resultssupporting
confidence: 77%
“…On the upper wing the lower side is split in two pressure levels and the lowest differential pressure is approximately at the maximum chord thickness. figure 4, below, the leading edge disturbance, on the right, and how far behind the trailing edge where laminar flow returns [11]. These match and support the results of pressure distribution in figure 3.…”
Section: Resultssupporting
confidence: 77%
“…It has been shown that the air drag can be reduced by 4-5% by engineering the surface with riblet structure of 62 µm [24]. Similarly, Stenzel et al proposed a paint based on aliphatic polyurethane resins that shows air-drag reduction of 6% [25].…”
Section: Wenzel Equation Is Written Asmentioning
confidence: 99%
“…Here, N is the total number of variables and each variable is chosen as, for instance, N = 4, x 1 = M ∞ , x 2 = Re ∞ , x 3 = P ∞ , and x 4 = α. a and b are coefficients for calculating the response surface. It should be noted that each variable would be non-dimensionalized prior to making a fitting curve using Equation (10). The cross terms in Equation (10) appear to introduce the curvature of the response surface since the fitting curve for this case would not be linear.…”
Section: Of 18mentioning
confidence: 99%
“…Among a number of boundary layer controlling devices such as suction [2,3], blowing [4], synthetic jets [5], vortex generators [6], and riblets [1,[7][8][9][10][11][12], riblets are one of the methodologies used to reduce aircraft surface drag [1,[7][8][9][10][11][12]. Riblets are a passive means of turbulent flow control by which skin friction drag is reduced, and were first employed at the NASA Langley Research Center back in the 1970s [8,13] in imitation of the skin structure of a shark that swims long distances at high speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation